Strategic analysis of the industrial enterprise functioning on the example of “KAMPO” company - A. A. Ilina; M. I. Zakirova (Вестник университета)
The article performs a strategic analysis of the functioning of an industrial enterprise, presents the results of the PEST – analysis of the industrial sector, considers measures to improve the financial stability of the enterprise of “KAMPO identifies and characterises the factors affecting the activity of the studied enterprise (SWOT – analysis), analyses its stability in the current market as a whole. Special attention has been paid to the key goals of this enterprise in various fields, as well as possible ways to improve the efficiency of “KAMPO”. In the final part of the article, it is concluded that there is a constant need to study enterprises in modern market conditions, their products, because the active participation of commodity producers in trade makes it possible to use available resources more effectively, join international achievements of science and technology, and allows identifying the existing strategic directions of their activities.